Soil Atlas of Africa - Jones, A.; Breuning-Madsen H; Brossard M; Dampha, A.; Deckers, J.; Dewitte, O.; Gallali T; Hallett S; Jones, R.; Kilasara M; Le Roux P; Micheli E; et al. (European Union, 2013)
What is soil? Where does soil come from? What is special about soil in Africa? What does soil provide to society and the environment? How do our activities affect soil? The first ever Soil Atlas of Africa uses striking maps, informative texts and stunning photographs to answer and explain these and other questions. Leading soil scientists from Europe and Africa have collaborated to produce this unique document. Using state of the art computer mapping techniques, the Soil Atlas of Africa shows the changing nature of soil across the continent. The Soil Atlas of Africa explains the origin and functions of soil, describes the different soil types that can be found in Africa and their relevance to both local and global issues. The atlas also discusses the principal threats to soil and the steps being taken to protect soil resources. The Soil Atlas of Africa is more than just a normal atlas. Rather, this volume presents an interpretation of an often neglected natural resource that surrounds and affects us all. The Soil Atlas of Africa is an essential reference to a non-renewable resource that is fundamental for life on this planet